Allergen immunotherapy for allergic rhinoconjunctivitis: a systematic overview of systematic reviews. Issue 1 (8th August 2017) - Nurmatov, Ulugbek; Dhami, Sangeeta; Arasi, Stefania; Roberts, Graham; Pfaar, Oliver; Muraro, Antonella; Ansotegui, Ignacio J.; Calderon, Moises; Cingi, Cemal; Durham, Stephen; van Wijk, Roy Gerth; Halken, Susanne; et al.
Abstract: Background: The European Academy of Allergy and Clinical Immunology (EAACI) is developing Guidelines on Allergen Immunotherapy (AIT) for Allergic Rhinoconjunctivitis (ARC). To inform the development of recommendations, we sought to critically assess the systematic review evidence on the effectiveness, safety and cost‐effectiveness of AIT for ARC. Methods: We undertook a systematic overview, which involved searching nine international biomedical databases from inception to October 31, 2015. Studies were independently screened by two reviewers against pre‐defined eligibility criteria and critically appraised using the Critical Appraisal Skills Programme (CASP) Systematic Review Checklist for systematic reviews. Data were descriptively synthesized. Results: Our searches yielded a total of 5932 potentially eligible studies, from which 17 systematic reviews met our inclusion criteria. Eight of these were judged to be of high, five moderate and three low quality. These reviews suggested that, in carefully selected patients, subcutaneous (SCIT) and sublingual (SLIT) immunotherapy resulted in significant reductions in symptom scores and medication requirements. Serious adverse outcomes were rare for both SCIT and SLIT. Two systematic reviews reported some evidence of potential cost savings associated with use of SCIT and SLIT. Conclusions: We found moderate‐to‐strong evidence that SCIT and SLIT can, in appropriately selected patients, reduce symptoms and medication requirements in patients with ARC with reassuring safety data. This evidence does however need to be interpreted with caution, particularly given the heterogeneity in the populations, allergens and protocols studied. There is a lack of data on the relative effectiveness, cost‐effectiveness and safety of SCIT and SLIT. We are now systematically reviewing all the primary studies, including recent evidence that has not been incorporated into the published systematic reviews.